Factors Affecting Older Workers' Willingness To Retire: A Survey Of Chinese State Enterprises - Qi, Zexing (2022)
As the ageing of the world's population is gradually accelerating today, the problem of ageing is particularly serious in China, a country with a large population. It is therefore necessary for contemporary organisations to pay attention to the retirement intentions of older workers in China and to explore and adopt appropriate methods to motivate older workers to work. This can allow them to become active again in the labour market to alleviate a number of problems associated with the ageing population. This study adopted a quantitative research approach by conducting a questionnaire survey on a sample of older workers in a state-owned enterprise in China. The data were then analyzed through various statistical methods. By comparing the results of the analysis with previous studies in the literature, the study found that demographic characteristics, career development, perceived health, perceived wealth, work-private life balance and perceptions of older workers were all related to the retirement intentions of older workers working in Chinese SOEs. Of these, the aspect of work-private life balance had the greatest impact on their intention to retire. The study also found that female older workers in Chinese SOEs were more likely to stay in their jobs than to choose to retire.